Effects of oxygen concentration variation on the structural and optical properties of reactive sputtered WOx thin film. (1st July 2021) - Mahjabin, Samiya; Mahfuzul Haque, Md.; Khan, Sobayel; Selvanathan, Vidhya; Jamal, M.S.; Bashar, M.S.; Alkhammash, Hend I.; Ismail Hossain, Mohammad; Shahiduzzaman, Md.; Amin, Nowshad; Sopian, Kamaruzzaman; Akhtaruzzaman, Md.
Highlights: The influence of Ar:O2 gas flow on O2 concentration in WOX film is investigated. O2 concentration also affects the WOX film's thickness. The impact of O2 concentration on the film's optical properties is discussed. WOX film is suitable as an electron transport layer for photovoltaic applications. 3D electromagnetic simulations investigate optics of perovskite solar cells. Abstract: Tungsten oxide (WOx ) has been widely investigated due to mainly its optoelectronic properties. This study primarily aimed to examine the influence of oxygen concentration on the structural and optical properties of WOx films. Herein, WOx thin films have been prepared by reactive sputtering method at low power (50 W) while controlling the Ar:O2 gas flow rate to vary oxygen concentration. Energy Dispersive X-ray (EDX) analysis reveals that the oxygen concentration depends on the gas flow rate. Such oxygen concentration changes affect the film's thickness, confirmed by the field emission scanning electron microscope (FESEM). Atomic force microscopy (AFM) analysis ensures the dependency of surface roughness of the films on the oxygen concentration. The developed films exhibit the amorphous state as validated by X-ray Diffraction (XRD) analysis. The Ultraviolet–Visible (UV–Vis) spectroscopy measurement was also conducted to determine transmittance and absorbance of the film, which further allows realizing necessary optical parameters, such as absorption coefficient, skin depth, energy bandgap, refractive index, extinction coefficient, etc. The oxygen concentration-dependent optical parameters are investigated in the spectral range of UV to near-infrared regions to ensure the use of WOx for optoelectronic device applications. Finally, we considered the optimized WOx film as a potential electron transport layer (ETL) to realize an efficient perovskite solar cell. The optics and optimization of this solar cell were studied by finite-difference time-domain (FDTD) simulations. The investigation allows us to calculate the maximum quantum efficiency (QE) and short-circuit current density (JSC ) of 90% and 22.1 mA/cm 2, respectively.